AidP, a novel N-Acyl homoserine lactonase gene from Antarctic Planococcus sp. - See-Too, W.S.; Ee, R.; Lim, Y.L.; Convey, P.; Pearce, D.A.; Yin, Wai Fong; Chan, Kok Gan (Nature Publishing Group, 2017)
Planococcus is a Gram-positive halotolerant bacterial genus in the phylum Firmicutes, commonly found in various habitats in Antarctica. Quorum quenching (QQ) is the disruption of bacterial cell-to-cell communication (known as quorum sensing), which has previously been described in mesophilic bacteria. This study demonstrated the QQ activity of a psychrotolerant strain, Planococcus versutus strain L10.15T, isolated from a soil sample obtained near an elephant seal wallow in Antarctica. Whole genome analysis of this bacterial strain revealed the presence of an N-acyl homoserine lactonase, an enzyme that hydrolyzes the ester bond of the homoserine lactone of N-acyl homoserine lactone (AHLs). Heterologous gene expression in E. coli confirmed its functions for hydrolysis of AHLs, and the gene was designated as aidP (autoinducer degrading gene from Planococcus sp.). The low temperature activity of this enzyme suggested that it is a novel and uncharacterized class of AHL lactonase. This study is the first report on QQ activity of bacteria isolated from the polar regions.